PENGARUH APLIKASI GEL THEOBROMINE TERHADAP KEKASARAN PERMUKAAN EMAIL GIGI DESIDUI PASCA DEMINERALISASI - Shoimah Alfa Makmur; Rinaldi Budi Utomo (Odonto : Dental Journal, 2019)
Background: Caries is common problem found in children. Caries prevalences increased mainly in developing countries such as Indonesia. Theobromine is an alkaloid compound in metilxantin group which can be found in the cocoa bean. Theobromine is believed to prevent caries by restoring the rough surface of email as the result of demineralisation. This research is aimed to analyze the eﬀect of theobromine gel on the surface roughness of deciduous teeth after demineralization.Method: It was laboratory experiments. Sample of research were 20 incisive cariesfree deciduous teeth. Samples divided into fve groups of treatments (concentration of gel theobromine 1%, 2%, 3%, 4%, and 5%). Each group consists of 4 samples. All samples were demineralized with 37% phosphoric acid for 60 seconds. Samples were immersed in artifcial saliva for 60 minutes in temperature 37⁰. Roughness examination before and after treatment was conducted using Surface Roughness Tester.Result: This experiment showed that surface roughness is decreasing after treated by fve diﬀerent concentrations of theobromine. There is a signifcant diﬀerence compared to other treatments (p<0,05).Conclusion: Theobromine can be used as one of the caries preventive products. The eﬀective concentration of gel theobromine to decrease surface roughness of teeth email is 5%.